DESIGNING KANTIN KEJUJURAN CORNER AT SMP NEGERI 1 KEMANG, BOGOR REGENCY - ANDAYANI ANDAYANI; Budi HERMAINI; Dian NOVITA; Monika HANDAYANI; Siti AISYAH (Diseminasi: Jurnal Pengabdian kepada Masyarakat, 2019)
Located in Tegal Village, Kemang District, Bogor Regency, SMP Negeri 1 Kemang is the only secondary school for the children from the surrounding villages. The local government has the expectation for the school to excel in various aspects, such as to develop the school to be a Secondary School with Exemplary Character. The development of Kantin Kejujuran (lit: Honesty Canteen) is expected to raise the students’ awareness of the importance of honesty. The development began in 2017, and it focused on the development of physical facilities. Along such development, initial assessment on the perception of students and teachers towards the value of honesty was conducted using the Likert scale. Open questionnaires were distributed to get the general idea of teachers and students’ expectation towards Kantin Kejujuran. In the designing process, it was found that there are similarities between the students’ and teachers’ perceptions towards the value of honesty, in which it is considered important and needs to be developed. The procedure of using Kantin Kejujuran in accordance with the characteristics of the students needed to be developed from 2018.